TNF Block Gene Variants Associate With Pain Intensity in Black Southern Africans With HIV-associated Sensory Neuropathy. Issue 1 (January 2016) - Hendry, Liesl M.; Wadley, Antonia L.; Cherry, Catherine L.; Price, Patricia; Lombard, Zané; Kamerman, Peter R.
Abstract : Objectives: HIV-associated sensory neuropathy (HIV-SN) is a common neurological complication of HIV infection, and it is often painful. Tumor necrosis factor (TNF)-α is implicated in neuropathic pain, but associations between neuropathic pain and polymorphisms in the TNFA gene have not been identified. The "TNF block" is a region of high linkage disequilibrium within the central major histocompatability complex that contains several genes involved in the regulation of inflammation, including TNFA . Polymorphisms in the block have been associated with an altered risk of HIV-SN, but no investigations into whether this region is associated with the painful symptoms of neuropathy have been undertaken. Therefore, we investigated whether polymorphisms in the TNF block are associated with pain intensity in black Southern Africans with HIV-SN. Methods: Single-nucleotide polymorphisms (SNPs) defining TNF block haplotypes and African-specific tagSNPs were genotyped in samples from 150 black Southern Africans with HIV-SN. Results: One SNP allele, rs28445017*A, was significantly associated with an increased pain intensity after correction for age, sex, and the CD4 T-cell count. A common 3-SNP haplotype containing rs28445017*G remained associated with a reduced pain intensity after correction for covariates and multiple comparisons. Discussion: We identified a novel genetic association between polymorphisms in the TNF block and the pain intensity in black Southern Africans with HIV-SN. Our study implicates rs28445017 in painful HIV-SN, although its precise role and whether it may be causative is unclear. rs28445017 was not associated with the risk for HIV-SN as such, highlighting potential differences between the pathophysiology of the neuropathy and the painful features of the neuropathy. Abstract : Supplemental Digital Content is available in the text.